The Accounting Reality of Electronic Payment Tools & Systems in the Economic Enterprise: Case Study ofNational Company for Marketing and Distribution of Petroleum Products (NAFTAL – Biskra-) - Guettaf, Okba; Boumaraf, Fatmazahra (Milev Journal of Research and Studies, 2021)
This study aims to identify the accounting reality for running the electronic payment system (NAFTAL CARD) in the National Company for Marketing and Distribution of Petroleum Products (NAFTAL), where the oil card, final payment device and management card were identified, in addition to the various applications and software used in The company's electronic payment process, and the steps followed by the company in the accounting management of the electronic payment system from the purchasing moment of a final electronic payment device, purchasing raw materials, card-making requirements, and transferring a final electronic payment device and cards from the General institution to the commercial units (NAFTAL - Biskra -) then deliver it to the customer, till the final use of the card by the customer. The results of the study concluded that the electronic payment system for the NAFTAL Card has achieved many advantages for the company, including: Achieving an additional business number as a result of selling electronic payment devices, management cards and NAFTAL Card, it also facilitated the process of controlling part of sales because all of its sales are electronically done, Providing liquidity to the company as a result of prepayment of the sales value. (card filling).